2021
DOI: 10.1021/acs.jafc.1c05206
|View full text |Cite
|
Sign up to set email alerts
|

Monooxygenase LaPhzX is Involved in Self-Resistance Mechanisms during the Biosynthesis of N-Oxide Phenazine Myxin

Abstract: Self-resistance genes are deployed by many microbial producers of bioactive natural products to avoid self-toxicity. Myxin, a di-N-oxide phenazine produced by Lysobacter antibioticus OH13, is toxic to many microorganisms and tumor cells. Here, we uncovered a self-defense strategy featuring the antibiotic biosynthesis monooxygenase (ABM) family protein LaPhzX for myxin degradation. The gene LaPhzX is located in the myxin biosynthetic gene cluster (LaPhz), and its deletion resulted in bacterial mutants that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Furthermore, although the phzNO1 Na overexpression strategy was performed, it had little effect on improving iodinin production. This may be indicated by the lack of self-resistance, efflux pump, or the low solubility of iodinin, , which greatly affected its production in P. chlororaphis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the phzNO1 Na overexpression strategy was performed, it had little effect on improving iodinin production. This may be indicated by the lack of self-resistance, efflux pump, or the low solubility of iodinin, , which greatly affected its production in P. chlororaphis.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, although the phzNO1 Na overexpression strategy was performed, it had little effect on improving iodinin production. This may be indicated by the lack of self-resistance, efflux pump, or the low solubility of iodinin, 49,50 which greatly affected its production in P. chlororaphis. Additionally, we suggested that strain adaptation evolution, enhanced precursor supply, fermentation strategy optimization, and protein engineering of phzNO1 La are all useful strategies to further improve the production of iodinin in P. chlororaphis.…”
Section: Conversion Of Pdc Into Dhp and Synthesis Module Optimizationmentioning
confidence: 99%
“…As mentioned earlier, aliphatic and aromatic N -oxides are known as prodrugs due to their ability to be reduced by various oxidoreductases expressed in bacterial and tumor cells. Moreover, the attention given to heterocyclic N -oxides, particularly quinoxaline derivatives, can be explained by the presence of this scaffold in natural bioactive compounds, such as iodinin, its analog myxin, echinomycin, and aspergilic acid [ 121 , 122 ].…”
Section: Chemotherapeutic Properties Of Quinoxaline 14-dioxidesmentioning
confidence: 99%
“…In this section, the attention is focused on the enzymatic synthesis of N-heteroaromatic N-oxides. The use of biological systems to obtain aromatic N-oxides is quite rarely reported, 15,[23][24][25][26] while the cases of non-heme diiron enzymes are even more limited. 27 Remarkably, monocyclic nitrogen compounds were among the best substrates of all tested compounds for PmlABCDEF monooxygenase (Pml).…”
Section: Transformation Of N-heteroaromatic Compounds Into N-oxidesmentioning
confidence: 99%